Commentary on ‘Mental Illness, Psychiatric Institutions, and the Singularity of Lives’ (Medicine Anthropology Theory, 2020)
‘Mental Illness, Psychiatric Institutions, and the Singularity of Lives’, a chapter of 'Affliction' by Veena Das (2015), illustrates the sociocultural, familial, and personal factors that determine the trajectory of mental illness from its onset to treatment. Das discusses two case histories: a young boy suffering from psychotic illness and a young girl in conflict with her father. Both of them come from families residing in the urban slums of a large Indian metropolis. Reading this chapter gave us an opportunity to ask: how are cultural issues handled in psychiatric clinical encounters in India, and how are these taught to young trainee psychiatrists? The chapter also made us curious about anthropological methods and research vis-à-vis psychiatry.